2015
DOI: 10.1111/trf.13439
|View full text |Cite
|
Sign up to set email alerts
|

The c.64_80del SMIM1 allele is segregating in the Hutterite population

Abstract: After emigrating to the United States and Canada, the Hutterite population has expanded dramatically. Alleles that initially entered the population have been maintained within the population. The c.64_80del null allele of SMIM1 is one such allele, thus having implications for transfusion medicine and child or maternal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The Hutterites are not an outbred population, but rather a genetic isolate exhibiting a strong founder effect (Coghlan and Zelinski, 2016). They are also an isolated population due to the communal farming, therefore variations of environmental factors have less impact on individuals’ microbiomes (Davenport et al, 2015; Igartua et al, 2016).…”
Section: Links Between Host Genetic Profile and Individual Gut Microbmentioning
confidence: 99%
“…The Hutterites are not an outbred population, but rather a genetic isolate exhibiting a strong founder effect (Coghlan and Zelinski, 2016). They are also an isolated population due to the communal farming, therefore variations of environmental factors have less impact on individuals’ microbiomes (Davenport et al, 2015; Igartua et al, 2016).…”
Section: Links Between Host Genetic Profile and Individual Gut Microbmentioning
confidence: 99%
“…Only three studies in Chinese individuals have reported genotyping methods to screen for Velgenotype, and few studies have reported the sequence of the gene or polymorphisms in the gene in Chinese individuals [13][14][15]. Because of the characteristics of Vel isoimmunization, the high frequency of Vel antigens in the Chinese (higher than 99.99%), and the lack of a monoclonal anti-Vel antibody, screening for the Vel antigen using molecular techniques and sequencing of the SMIM1 gene should be carried out routinely [7,16,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial kits were used to examine exons 3 and 4 of the SMIM1 gene (Vel blood group sequence kit; Libiotech). Briefly, the PCR tubes contained 36 lL PCR matrix buffer, 0.32 lL Taq polymerase (5U/lL; Promega, USA), 4 lL genomic DNA(concentration: 20-100 ng/lL) and 2 lL primers(10 lM/lL) [16]. The cycling conditions were as follows: 2 min initial denaturation at 96°C; five cycles of 20 s at 96°C and 1 min at 68°C; 10 cycles of 20 s at 96°C, 50 s at 65°C, and 45 s at 72°C; 17 cycles of 20 s at 96°C, 50 s at 62°C, and 45 s at 72°C; and a final 2 min at 72°C.…”
Section: Molecular Analysis Of the Smim1 Genementioning
confidence: 99%
“…For example, a mutation causing weak expression of the Vel antigen has been noted in Hutterites (an ethnoreligious community in western Canada with origins in Germany and Eastern Europe). 5 Unique blood group mutations have also been noted in those of Indigenous and French Canadian descent. 6,7 Given the diversity of the population, a robust program is needed to meet the rare blood needs of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Specific mutations have also been identified in various populations within Canada. For example, a mutation causing weak expression of the Vel antigen has been noted in Hutterites (an ethnoreligious community in western Canada with origins in Germany and Eastern Europe) 5 . Unique blood group mutations have also been noted in those of Indigenous and French Canadian descent 6,7 .…”
Section: Introductionmentioning
confidence: 99%